Oxygen Availability in Respiratory Muscles During Exercise in Children Following Fontan Operation - Stöcker, Fabian; Neidenbach, Rhoia; Fritz, Celina; Oberhoffer, Renate M.; Ewert, Peter; Hager, Alfred; Nagdyman, Nicole (Frontiers in Pediatrics, 2019)
Introduction: As survival of previosly considered as lethal congenital heart disease forms is the case in our days, issues regarding quality of life including sport and daily activities emerge. In patients with Fontan circulation, there is no pump to propel blood into the pulmonary arteries since the systemic veins are directly connected to the pulmonary arteries. The complex hemodynamics of Fontan circulation include atrial function, peripherial muscle pump, integrity of the atrioventricular valve, absence of restrictive or obstructive pulmonry lung function. Therefore, thoracic mechanics are of particular importance within the complex hemodynamics of Fontan circulation. Methods: To understand the physiology of respiratory muscles, the aim of this study was to examine the matching of auxiliary respiratory muscle oxygen delivery and utilization during incremental exercise in young male Fontan patients (n=22, age=12.04 ± 2.51) and healthy Controls (n=10, age=14.90 ± 2.23). All subjects underwent a cardiopulmonary exercise test (CPET) to exhaustion whereas respiratory muscle oxygenation was measured noninvasively using a near-infrared spectrometer (NIRS). Results: CPET revealed significantly lower peak power output, oxygen uptake and breath activity in Fontan patients. The onset of respiratory muscle deoxygenation was significantly earlier. The matching of local muscle perfusion to oxygen demand was significantly worse in Fontans between 50% and 90% V̇O2peak. Findings: The results indicate that (a) there is high strain on respiratory muscles during incremental cycling exercise and (b) auxiliary respiratory muscles are worse perfused in patients who underwent a Fontan procedure compared to healthy Controls. This might be indicative of a more general skeletal muscle strain and worse perfusion in Fontan patients rather than a localized-limited to thoracic muscles phenomenon.